2022
DOI: 10.1007/s10341-022-00784-6
|View full text |Cite
|
Sign up to set email alerts
|

Internal Factors Affecting Competitiveness in Agribusinesses: A Case Study in the Hazelnut Sector in Ordu and Giresun Provinces of Turkey

Abstract: The study’s primary purpose is to reveal the factors affecting the competitiveness of hazelnut agribusiness enterprises. The data used in the research were obtained from surveys with 51 enterprises in Ordu and Giresun provinces, Turkey. The enterprises were divided into competitive and non-competitive with a two-step cluster analysis. Indices were calculated to measure enterprises’ competitiveness, and the t‑test was used to compare enterprises’ characteristics and competitiveness values. The research results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Sidhu and Kaur (2006), Bairwa et al (2014), Verma et al (2017), and Veni and Lakshmi (2018) all noticed similar trends in their studies. The results of another study showed that the effectiveness of a company's competitiveness was affected by both internal and external factors (Aydoğan, 2022). Also, they found that small cooperatives were the most successful and that large cooperatives had untapped potential.…”
Section: Competitionmentioning
confidence: 99%
“…Sidhu and Kaur (2006), Bairwa et al (2014), Verma et al (2017), and Veni and Lakshmi (2018) all noticed similar trends in their studies. The results of another study showed that the effectiveness of a company's competitiveness was affected by both internal and external factors (Aydoğan, 2022). Also, they found that small cooperatives were the most successful and that large cooperatives had untapped potential.…”
Section: Competitionmentioning
confidence: 99%